A General Strategy for Hollow Metal‐Phytate Coordination Complex Micropolyhedra Enabled by Cation Exchange. Issue 47 (11th September 2020) - Chen, Meiling; Peng, Chenxi; Su, Yaoquan; Chen, Xue; Zhang, Yuezhou; Wang, Yu; Peng, Juanjuan; Sun, Qiang; Liu, Xiaowang; Huang, Wei
Abstract: The ability to incorporate functional metal ions (M n + ) into metal–organic coordination complexes adds remarkable flexibility in the synthesis of multifunctional organic–inorganic hybrid materials with tailorable electronic, optical, and magnetic properties. We report the cation‐exchanged synthesis of a diverse range of hollow M n + ‐phytate (PA) micropolyhedra via the use of hollow Co 2+ ‐PA polyhedral networks as templates at room temperature. The attributes of the incoming M n +, namely Lewis acidity and ionic radius, control the exchange of the parent Co 2+ ions and the degree of morphological deformation of the resulting hollow micropolyhedra. New functions can be obtained for both completely and partially exchanged products, as supported by the observation of Ln 3+ (Ln 3+ =Tb 3+, Eu 3+, and Sm 3+ ) luminescence from as‐prepared hollow Ln 3+ ‐PA micropolyhedra after surface modification with dipicolinic acid as an antenna. Moreover, Fe 3+ ‐ and Mn 2+ ‐PA polyhedral complexes were employed as magnetic contrast agents. Abstract : The cation exchanged synthesis of diverse hollow metal‐phytate (PA) polyhedral complexes is reported using hollow Co 2+ ‐PA micropolyhedra as templates in a liquid phase. The synthetic strategy enables facile addition of multiple functionalities within the metal‐PA polyhedral networks with simultaneous control of their physicochemical features under mild conditions.